Swimming and Persons with Mild Persistant Asthma - Mirjana Arandelovic; Ivana Stankovic; Maja Nikolic (The Scientific World Journal)
The aim of our study was to analyze the effect of recreational swimming on lung function and bronchial hyperresponsiveness (BHR) in patients with mild persistent asthma. This study included 65 patients with mild persistent asthma, who were divided into two groups: experimental group A (n = 45) and control group B (n = 20). Patients from both groups were treated with low doses of inhaled corticosteroids (ICS) and short-acting β2 agonists salbutamol as needed. Our program for patients in group A was combined asthma education with swimming (twice a week on a 1-h basis for the following 6 months). At the end of the study, in Group A, we found a statistically significant increase of lung function parameters FEV1 (forced expiratory volume in 1 sec) (3.55 vs. 3.65) (p < 0.01), FVC (forced vital capacity) (4.27 vs. 4.37) (p < 0.05), PEF (peak expiratory flow) (7.08 vs. 7.46) (p < 0.01), and statistically significant decrease of BHR (PD20 0.58 vs. 2.01) (p < 0.001). In Group B, there was a statistically significant improvement of FEV1 3.29 vs. 3.33 (p < 0.05) and although FVC, FEV1/FVC, and PEF were improved, it was not significant. When Groups A and B were compared at the end of the study, there was a statistically significant difference of FVC (4.01 vs. 4.37), FEV1 (3.33 vs. 3.55), PEF (6.79 vs.7.46), and variability (p <0.001), and statistically significantly decreased BHR in Group A (2.01 vs. 1.75) (p < 0.001). Engagement of patients with mild persistent asthma in recreational swimming in nonchlorinated pools, combined with regular medical treatment and education, leads to better improvement of their parameters of lung function and also to more significant decrease of their airway hyperresponsiveness compared to patients treated with traditional medicine